Tradition as testimony : the meanings of witness in German Evangelical-Catholic dialogues from the 1980s to the 2020s - Heikkilä, Ida, 1986-; Helsingin yliopisto. Teologinen tiedekunta (Helsinki : Helsingin yliopisto, teologinen tiedekunta, 2023)
This study presented analysis of the meanings of witness in German Evangelical-Catholic dialogues from the 1980s to the 2020s. The term "Evangelical" was used for the German "evangelisch", referring to Lutheran, Reformed and United Churches. The main sources of this study were documents issued by the Ökumenischer Arbeitskreis Evangelischer und Katholischer Theologen (ÖAK) and the Bilaterale Arbeitsgruppe der Deutschen Bischofskonferenz und der Kirchenleitung der Vereinigten Evangelisch-Lutherischen Kirche Deutschlands (BA). Within the timeline of this research, the ÖAK published 18 dialogue documents, BA 3. In these documents, the idea of witness was expressed through the words "Zeuge", "Zeugnis" and "bezeugen", as well as their inflected forms. The secondary sources of this study consisted of 1) two contemporary documents issued by the World Council of Churches and 2) the most central doctrinal documents of the Roman Catholic, Lutheran and Reformed Churches. A comparison between the primary and secondary sources afforded the larger context of the study. The method used in this study was systematic analysis, a text-based approach examining the sources intrinsically as independent unities and extrinsically in their historical and theological contexts. Then, the results of the analysis were presented by means of a communication triangle distinguishing between (i) the witnessing thing or person, (ii) the testimony that is borne and (iii) the audience of the witness.
In the primary sources, the event of God's self-attestation was the starting point for all human witness. God attests Himself at countless points of history, but definitively only in the Incarnation. Human beings have access to God's self-attestation only in a mediated form, through human testimony. Among all testimonies, the apostolic testimony is normative. From this perspective, the ecclesial tradition is a historical signifying or mediating form of Tradition, the unceasing actualization of God's revelation in the Spirit. The unity of the historical testimonies is maintained in anamnesis, where human memory becomes a divine memory in which the past events of salvation become actual and present. This study designated this conception of witness as "traditio-historical". The conception was found to resonate with the theology of the Second Vatican Council, and also with Wolfhart Pannenberg's revelation theology. This understanding of witness described above had a direct impact on the dialogue groups' understanding of unity and the goal of ecumenism. From their points of view, different ecclesial traditions were testimonies that reflected Tradition in their own way. Even when separated, churches could bear a common witness to the one truth of God. Some of the members of the ÖAK, especially the Roman Catholic Walter Kasper, leaned towards an actualistic conception of witness that entailed the conviction that the word of God cannot be identified with anything immanent - not with the Scriptures, nor with proclamation, nor even with the Sacraments. Instead, these are signs that point away from themselves, towards a transcendent God. The central elements of this conception are also found in Karl Barth's revelation theology. At times, this actualistic conception found its way into the common statements of the ÖAK.
From the perspective of communication theory, the earliest texts of the dialogue groups focused on the second of the points of the communication triangle, the content of the apostolic testimony, whereas the most recent dialogues emphasized the first point, the subject of witness. The analysis also showed that in the German dialogues, the second point of the communication triangle typically splits into a duality of signum and res, where the res that is attested is Jesus Christ but the signa mediating this content vary. The comparison between the German dialogues and the dialogues of the World Council of Churches demonstrated that the global, multilateral conceptions of witness and the German, bilateral conceptions of witness focused on different aspects of witness as understood in the New Testament: the former focused on "martyria" as action, the latter on "martyria" as the testimony that is borne to the apostolic Gospel. This study argued that the German Catholic-Evangelical conception of witness is best expressed in English by a distinction between "witness" as the subject that bears witness and "testimony" as the content that is mediated by that witness.
Väitöskirja
Väitöskirja
Sisältää bibliografisia viitteitä.
Keywords: ekumenia; historia; luterilaiset kirkot; reformoidut kirkot; roomalaiskatolinen kirkko; teologia; ykseys; Saksa; doktorsavhandlingar; väitöskirjat; 1980-luku.; 1990-luku.; 2000-luku (vuosikymmen); 2000-talet (årtionde); 2010-luku.; 2020-luku.